Molecular Mechanisms of L1 and NCAM Adhesion Molecules in Synaptic Pruning, Plasticity, and Stabilization - Duncan, Bryce W.; Murphy, Kelsey E.; Maness, Patricia F. (Frontiers in Cell and Developmental Biology, 2021)
Mammalian brain circuits are wired by dynamic formation and remodeling during development to produce a balance of excitatory and inhibitory synapses. Synaptic regulation is mediated by a complex network of proteins including immunoglobulin (Ig)- class cell adhesion molecules (CAMs), structural and signal-transducing components at the pre- and post-synaptic membranes, and the extracellular protein matrix. This review explores the current understanding of developmental synapse regulation mediated by L1 and NCAM family CAMs. Excitatory and inhibitory synapses undergo formation and remodeling through neuronal CAMs and receptor-ligand interactions. These responses result in pruning inactive dendritic spines and perisomatic contacts, or synaptic strengthening during critical periods of plasticity. Ankyrins engage neural adhesion molecules of the L1 family (L1-CAMs) to promote synaptic stability. Chondroitin sulfates, hyaluronic acid, tenascin-R, and linker proteins comprising the perineuronal net interact with L1-CAMs and NCAM, stabilizing synaptic contacts and limiting plasticity as critical periods close. Understanding neuronal adhesion signaling and synaptic targeting provides insight into normal development as well as synaptic connectivity disorders including autism, schizophrenia, and intellectual disability.